Effect of plant establishment method and weeding on the yield and yield components of Boro rice (Progressive Agriculture, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, Bangladesh during December 2013 to May 2014 to observe the effect of plant establishment method and weeding on the yield and yieldcomponents of boro rice cv. BRRI dhan29. The treatments included two plant establishment methods  viz. direct seeding and transplantingusing the seedling of direct seeded plots; four weedings viz. no weeding, one weeding at 15 days after transplanting (DAT), two weedings at 15 and 30 DAT, three weedings at 15, 30 and 45 DAT.The experiment was laid out in a randomized complete block design with four replications. Yield contributing characters and yield of boro rice were influenced by plant establishment method and weeding. The highest plant height (79.24 cm), grains panicle-1 (121.90), grain yield (2.86 t ha-1), straw yield (3.56 t ha-1), biological yield (6.42 t ha-1) and harvest index (44.81%) were recorded by transplanting method. The highest number of total tillers hill-1 (17.48 ), effective tillers hill-1 (13.39), grain yield (3.38 t ha-1), straw yield (4.22 t ha-1), biological yield (7.61 t ha-1) and harvest index (47.01%) were obtained with three weeding at 15, 30 and 45 DAT. The lowest grain yield (1.69 t ha-1) and straw yield (2.42 t ha-1) were recorded from no weeding. The highest grain yield (3.65 t ha-1) was recorded from transplanting method with three weeding, which was statistically similar to transplanting method with two weeding. Again direct seeding method with three weeding resulted in similar yield with that of transplanting method with two weeding. The lowest grain yield (1.46 t ha-1) was recorded from direct seeding method with no weeding. From the present experiment it may be concluded that transplanting method with two weeding or direct seeding method with three weeding may be recommended for cultivation of modern bororice.Progressive Agriculture 27 (1): 27-31, 2016